Analisis Dinamik Model Matematika pada Terapi Gen untuk Pengobatan Kanker dengan Waktu Tunda - Maya Sari Wahyuni; Rahmat Syam; Sulaiman Sulaiman (Seminar Nasional LP2M UNM, 2019)
Abstract. Cancer or commonly also called malignant tumor is one of the deadliest killer of mankind. The types of cancer treatment has been developed by many scientists, one of them is treatment by gene therapy. Using the mathematical equation, Lotka-Volterra equations can be formed a new equation for the interaction between effector cells and cancer cells. In the development and growth of cancer cells undergo several phases that will bring the process delay (τ). So the goal of this paper is to establish a mathematical equation on gene therapy for the treatment of cancer as a result of the delay (time delay), to determine and analyze the stability of the equilibrium point and simulate it. Keywords: effector cells, cancer cells, delay, equilibrium, Lotka-Volterra